Probabilistic reasoning in multiagent systems : a graphical models approach - Xiang, Yang, 1954- (Cambridge University Press, 2002)
This book identifies the technical challenges in building intelligent agents that can cooperate on complex tasks in an uncertain environment and provides a rigorous framework for meeting these challenges. It is the first book that addresses the subject of probabilistic inference by multiple agents using graphical knowledge representations.